KONSTRUKSI REALITAS MAKNA “ BAJAPUIK” PADA PERNIKAHAN BAGI PEREMPUAN PARIAMAN DI KECAMATAN PASIR PENYU - Bunga Moeleca; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Tradition bajapuik (japuik, shuttle) is a tradition that marriage is a trade mark of Pariaman area. Tradition bajapuik seen as the duty of the woman's family gave a number of items or money to men (future husband) before the ceremony performed. This study raises a bajapuik tradition which has grown in the district Sand Turtle. This study aims to determine the motive, knowledge and experience as well as the values contained in bajapuik tradition.This study used a qualitative method with phenomenological approach Schutz. The subjects were 10 women in sub pariaman turtle sand and selected by the snowball technique. To get the data, the authors used three data collection techniques, ie observation, in-depth interviews, and documentation. This study uses data analysis techniques phenomenological research according to Creswell, using the techniques of observation perseverance, the extension of participation, and the adequacy of reference.Results showed that women have a motive pariaman motivated by motives